The effect of spent mushroom (Agaricus bisporus) compost on the indigenous rhizosphere microbiota in strawberry cultivation - Elaamer, Hani (SLU/Dept. of Agricultural Biosystems and Techology, 2020)
Spent mushroom compost (SMC) is a by-product of mushroom cultivation with the potential to be used in the cultivation system to suppress plant pathogens, enhance water holding capacity, increase soil water aeration and to improve the soil structure through the input of organic matter and additional nutrients. The electric conductivity (EC) as well as pH recorded high values in the SMC, which is a challenge for its application in food production systems. For the successful use of SMC as a plant growth promoter and diseases suppressive factor, more knowledge about the effect of its amendment to the soil or the growing media is needed. Strawberry cultivation is one of the major production systems within the Swedish Horticultural sector with challenges regarding root pathogens. Suppressive growing media or compost are a strategy of great interest to face this challenge. The current study was carried out to investigate the effect of SMC proportional amendment on the suppressive potential of the growing media and its indigenous rhizosphere microbiota, plant growth, and nutrient content in strawberry cultivation. Five treatments (proportions) with six replicates per treatment were included in the experiment; G1= peat (100%), G2= SMC (100%), G3= SMC (30%): Peat (70%), G4= SMC (50%): Peat (50%) and G5= SMC (70%): Peat (30%). The results give a preliminary understanding of the types of beneficial microbes that occurs in the cultivation system after the amendment of SMC. Utilization of spent mushroom compost enhanced the abundance of nutrient content in the strawberry rhizosphere by increasing the availability of macro and microelements needed for plant growth. It also created a rich microbiota of several microbial groups known for its antagonistic potential such as Trichoderma spp., Bacillus spp., Pseudomonas spp., and Actinomyces spp. the highest abundance of microbes was in the G4 treatment except for the Actinomyces spp. and Trichoderma spp. the G3 treatment was the highest treatment with respect to beneficial effects on plant height and number of leaves. The presence of microorganisms known by their antagonistic properties against plant pathogens and the enzyme activities performed by these microorganisms is an indication of the suppressive effect developed in the growing media after the addition of SMC. The abundance of Trichoderma spp. increased by the increase of SMC in the treatments.